Transformation of struvite from wastewater to a hydrogen fuel storage compound ammonia borane - Dingra, Nin; Witty, Michael; Celis, Marie; Boppana, Narendra; Ayudhya, Theppawut (Frontiers in Chemistry, 2023)
Ammonia borane (NH3BH3) is a carrier of hydrogen gas that is known as a carbon-free renewable energy source. A high hydrogen content of ammonia borane and its stability in air at ambient temperatures make it a valuable molecule for its potential use as a hydrogen storage compound. In this study, we investigate a new approach for synthesizing ammonia borane using wastewater-derived ammonia source. Wastewater recycling has always been a global interest towards sustainability. In addition to reclaiming the water, recycling nutrients in wastewater is a topic of interest. Nutrients such as nitrogen, magnesium, and phosphorous are readily recovered from wastewater as struvite (NH4MgPO4•6H2O). This new process involves converting urine into struvite, and then reacting struvite with alkali borohydrides to produce a high-purity ammonia borane. The use of mild reaction conditions without extensive purification process, together with high purity ammonia borane product make this process a desirable course of action for recycling the nitrogen waste. In the course of moving towards a sustainable environment, the energy and wastewater industries will benefit from this combined process of nitrogen removal from wastewater to generate a renewable carbon-free energy molecule.